2016
DOI: 10.1002/2016jd025656
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the upper tropospheric outflow in Hurricanes Iselle and Julio (2014) in the Navy Global Environmental Model (NAVGEM) analyses and in satellite and dropsonde observations

Abstract: Upper tropospheric outflow was examined during the life cycles of two hurricanes in the eastern and central Pacific Ocean. The outflow from Hurricanes Iselle and Julio was evaluated by using analyses from the Navy Global Environmental Model, which were very highly correlated with satellite atmospheric motion vector and NOAA G‐IV dropsonde observations. A synoptic overview provided the environmental context for the life cycles of both tropical cyclones (TCs). Then, the outflow magnitude and direction within 6 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Generally, a trough north or west of a TC will reduce I by reducing both z and y t , thereby creating an environment more favorable for the development of outflow. While the direction of positive y r is often broadly consistent with the direction of lower I, Barrett et al (2016) find the strongest outflow to occur 458-908 to the right of the minimum I. They attribute this phenomenon to the fact that the outflow is modifying its own environment by reducing (enhancing) the y t term in the equation for I counterclockwise (clockwise) of the region of strongest outflow.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Generally, a trough north or west of a TC will reduce I by reducing both z and y t , thereby creating an environment more favorable for the development of outflow. While the direction of positive y r is often broadly consistent with the direction of lower I, Barrett et al (2016) find the strongest outflow to occur 458-908 to the right of the minimum I. They attribute this phenomenon to the fact that the outflow is modifying its own environment by reducing (enhancing) the y t term in the equation for I counterclockwise (clockwise) of the region of strongest outflow.…”
Section: Introductionmentioning
confidence: 79%
“…TCs primarily interact with environmental flow at upper levels where I is weaker, as I is a measure of the resistance to motion in the radial direction (Schubert and Hack 1982;Shapiro and Willoughby 1982;Hack and Schubert 1986). Therefore, a reduction in I may allow stronger radial outflow to develop in the direction of low I (Holland and Merrill 1984;Rappin et al 2011;Molinari and Vollaro 2014;Barrett et al 2016). Molinari and Vollaro (2014) find positive radial wind y r to be maximized at the outer edge of the inertially unstable (I , 0) region and hypothesize that the length of time that the inertially unstable region persists may be related to the nature or length of the period of TC intensification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the asymmetric structure [36,37], low Richardson number [38,39], and weaker inertial instability [40][41][42][43] of the TC upper-level outflow, the outflow can easily interact with the upper-level larger-scale environment and the inner-core of a TC, thereby playing a mediating role between the environment and the storm core [41]. As such, it can affect the secondary circulation and, consequently, the TC intensity [37,41,[43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has further demonstrated that outflow tends to develop in regions where upper-tropospheric inertial stability is low, and stronger outflow tends to be associated with intensifying TCs (Rappin et al 2011;Barrett et al 2016;Komaromi and Doyle 2017). Synoptic-scale forcing has been found to further reduce upper-tropospheric inertial stability, which favors intensification (Rappin et al 2011).…”
mentioning
confidence: 99%